Adverse effects associated with favipiravir in patients with COVID-19 pneumonia: a retrospective study - Ergür, Figen Öztürk; Yıldız, Murat; Şener, Melahat Uzel; Kavurgacı, Suna; Ozturk, Ayperi (São Paulo Medical Journal, 2022)
BACKGROUND: Favipiravir is generally used in treating coronavirus disease 2019 (COVID-19) pneumonia in Turkey. OBJECTIVE: To determine the side effects of favipiravir and whether it is a good treatment option. DESIGN AND SETTING: Retrospective study conducted in Atatürk Chest Diseases and Chest Surgery Training and Research Hospital, Ankara, Turkey. METHODS: 357 patients who completed favipiravir treatment at the recommended dose were included 37 patients with drug side effects and 320 patients without drug side effects were examined in two groups. RESULTS: Side effects were observed in 37 (10.36%) out of 357 patients using favipiravir. The most common side effect was liver dysfunction, in 26 (7.28%) of the patients. The following other side effects were also observed: diarrhea (1.4%), nausea (0.84%), abdominal pain (0.28%) and thrombocytopenia (0.28%). One patient (0.28%) presented both increased transaminases and nausea. CONCLUSION: In this study, it was determined that favipiravir may constitute an alternative for treating COVID-19 pneumonia given that its side effects are generally well tolerated and not serious.